Vozes na rua: práticas de leitura e escrita e construção de uma nova imagem do morador em situação de rua - Magna Luzia Diniz Matos dos Santos (2009)
The main objective of this dissertation is to verify how reading and writing practices contribute to the construction of a better image of individuals in street situation through their discourse. For theoretical support, authors such as Bakhtin, Benveniste, Ducrot,Maingueneau, Fairclough, van Dijk, Goffman, DaMatta, Hall, Woodword, Tadeu Silva and other researchers were adopted as reference in this approach to language, enunciation, polyphony, dialogism, text, discourse, intertextuality, interdiscursivity, ideology, identity andethos. Foucambert, Smith, Freire, Walty and Soares introduced the conceptions and functions of reading and writing. Escorel, Snow and Anderson, Vieira, Bezerra and Rosa contributed with studies about street populations. The object of the analysis are the written records of 118testimonies, taken from fourteen interviews with individuals who live or have lived in the streets and who are taking or have taken part in reading and writing practices offered to this social group. This material made it possible to identify the representations or stereotypespresent in the discourse of people in street situation; the practices of reading and writing more common to the group interviewed and the functions or value given to these practices; how thepractices of reading and writing reflect in the reconstruction of a better image of these individuals. The analysis makes it possible to conclude that the individual in street situation uses a polyphonic discourse to dispel stereotypes and construct a better image of his or herself. Despite being an excluded social group, a small number of these individuals have been seeking social reinsertion through participation in reading and writing practices promoted by institutions such as the ones that publish the magazine Revista Ocas and the newspapers Bocade Rua and O Trecheiro.